PROTRET KAUM PEREMPUAN PRA-ISLAM DALAM AL-QUR'AN - Abad Badruzaman (QOF, 2019)
This article intended to reveal the description of pre-Islamic women as far as the Qur’an is taken. This was done to provide a foundation of insight that how true Islam greatly elevates the dignity and status of women. Because the discussion in this paper links a theme that is in the Koran, the method used refers to the framework of the interpretation method maudhu’i (thematic). Operationally, in this article verses about pre-Islamic women was inventoried and then organized into several subthemes which all refer to the main theme, namely pre-Islamic women. The results of the discussion by thematizing the verse shows that: first, Islam highly upholds women and gives equal status to men. Second, Islam also gives women adequate and free space to play a role in the public sphere. Third, related to the situation of women in the pre-Islamic era to the extent recorded by the Koran shows that they were oppressed at that time. A number of their rights are not granted or reduced by the ignorance system which is in favor of only men. The culmination of the cruel behavior of the ignorance system towards women is their habit of being surly when their wives give birth to baby girls, even at the extreme level they are buried alive because they are considered disgrace.